Regional Unemployment and its Persistence in Transition Countries - Fabian Bornhorst; Simon Commander (Institute for the Study of Labor (IZA), 2004)
We look at the differences in regional unemployment rates in six major transition countries and their persistence over time. We analyse the role various adjustment mechanisms play. While movement out of the labour force seems to be one consequence in many regions with high relative unemployment, there are also signs of emerging wage flexibility. Employment creation, by contrast, has not picked up in regions of high unemployment. Labour mobility also remains very limited in size although it appears to respond to basic economic incentives. Policies addressing housing market imperfections and information asymmetries are necessary to increase worker mobility and to integrate better national labour markets.
Keywords: P2; J61; 330; transition; regional unemployment; mobility; Regionale Arbeitslosigkeit; Hysteresis; Übergangswirtschaft; Regionale Arbeitsmobilität; Lohnrigidität; Schätzung; Bulgarien; Tschechische Republik; Ungarn; Polen; Rumänien; Russland